Effectiveness of the MathShark Application in Enhancing Students’ Problem-Solving Skills in Exponent Learning: A STEM-Integrated Approach - Inaz Iffarani Sofiana; Ali Shodikin (Journal of Mathematical Pedagogy (JoMP), 2025)
Learning exponent concepts remains challenging for middle school students, particularly in developing problem-solving skills. This study aimed to examine the effectiveness of the MathShark game-based application integrated with a STEM approach compared to conventional mathematics instruction. A quasi-experimental design with a pretest–posttest control group was employed. The participants consisted of two groups of middle school students: an experimental group using the MathShark application and a control group receiving traditional instruction. Data were collected through problem-solving tests and analyzed using the Mann–Whitney U test and the Wilcoxon Signed-Rank test. The results indicated a significant improvement in students’ problem-solving skills in the experimental group compared to the control group (p < 0.05). These findings suggest that integrating game-based applications within a STEM framework has a positive effect on students’ understanding of exponent concepts and their problem-solving abilities.